IgG4 autoantibodies and autoantigens in the context of IgG4-autoimmune disease and IgG4-related disease - Motta, Rodrigo V.; Culver, Emma L. (Frontiers in Immunology, 2024)
Immunoglobulins are an essential part of the humoral immune response. IgG4 antibodies are the least prevalent subclass and have unique structural and functional properties. In this review, we discuss IgG4 class switch and B cell production. We review the importance of IgG4 antibodies in the context of allergic responses, helminth infections and malignancy. We discuss their antiinflammatory and tolerogenic effects in allergen-specific immunotherapy, and ability to evade the immune system in parasitic infection and tumour cells. We then focus on the role of IgG4 autoantibodies and autoantigens in IgG4-autoimmune diseases and IgG4-related disease, highlighting important parallels and differences between them. In IgG4-autoimmune diseases, pathogenesis is based on a direct role of IgG4 antibodies binding to self-antigens and disturbing homeostasis. In IgG4-related disease, where affected organs are infiltrated with IgG4-expressing plasma cells, IgG4 antibodies may also directly target a number of self-antigens or be overexpressed as an epiphenomenon of the disease. These antigen-driven processes require critical T and B cell interaction. Lastly, we explore the current gaps in our knowledge and how these may be addressed.